Pengaruh Gaya Belajar, Minat, Dan Motivasi Sebagai Variabel Moderating Terhadap Hasil Belajar Mata Pelajaran Akuntansi Syariah - Indra Permata Alfiando; Luqman Hakim (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2021)
Student learning outcomes at this time are the effect of multiple factors which can be internal and external. The purpose of this study is to analyze the effects of variables (learning style, interest in learning, and motivation to learn) in class XI students of Islamic Banking at SMK Negeri 2 Mojokerto. The type of this research is quantitative. The population in this study were 118 students of class XI Islamic Banking at SMK Negeri 2 Mojokerto and the samples were taken by means of a possible sample using a simple random sampling method. After taking the data, the results obtained explain that the results of the t test variable Learning Style in this study have a result of 5,359 with a significance result of 0,000 or can be said to be below 0.05. The result of the t test for the Learning Interest variable in this study has a result of 3,314 and a significance result of 0,000 or it can be said that it is below 0.05 so that the researcher concludes that H0 is not accepted while Ha is not rejected. The results of the t-test variable Learning Motivation as a moderating variable in this study have a result of 2.114 followed by a significance value of 0.37 or can be said to be below 0.05. Validity testing uses a significance of 5% provided that all variables r count is greater than r table 0.361 which means it can be declared valid. So (1) there is an effect of learning style, (2) there is an effect of interest in learning, (3) there is an effect of learning motivation as a moderating variable, (4) there is an effect of student learning outcomes in class XI Islamic banking SMK Negeri 2 Mojokerto.